Peranan Sistem Teknologi Informasi Pada Pembiayaan Di Masa Pandemi Covid-19 di PT. BPRS Puduarta Insani - Azhari, Farah Indah; Dalimunte, Ahmad Amin (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Considering the importance of the role of information technology in companies where companies must continue to strive to increase their potential in business, especially during this pandemic, they must do their best for their company's business in order to attract people's attention. Financial institutions in Indonesia, including banks, are faster and more intensive than other sectors or types of industry in applying computer technology in providing services to customers. The purpose of this study was to find out how the role of information technology systems in financing during the COVID-19 pandemic at PT BPRS Puduarta Insani. Which is where the role of this information technology system is very necessary and very important where information technology is very helpful and also facilitates all activities in the bank. The method used is a qualitative type method. how the approach used by researchers in this study is a qualitative approach with a descriptive type, which displays data and data results as they are without a manipulation process which only describes situations and events that come from interviews and observations.